Forensic expertise on issues of intellectual property law: specific procedure - Boiarchuk, Oleksandr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article contains the results of research on establishing the specifics of forensic examination on intellectual property law. The legislative definitions of the concept of "forensic expertise" are analyzed, in addition, the scientific positions of national scientists on the definition of the concept of forensic expertise are indicated. The legal consolidation of the right to intellectual property and creative activity in the Basic Law of the country is provided. Intellectual and creative activity is distinguished, the primacy of the origin of the concept is established.The scientific and legislative period of the establishment and development of forensic expertise on intellectual property rights is singled out, namely, from 2002 to today, the system continues to develop together with society and the most important normative legal act, which became the beginning of the development of forensic expertise on intellectual property rights. Special types of research objects, which are subject to forensic examination, are given.The expert specialties that a forensic expert must possess in order to conduct forensic examinations on intellectual property law are defined. Official statistical data on the commission of criminal offenses by specific objects, which are more developed today, are indicated. Forensic expertise on intellectual property law is classified according to the following system criteria: by the available number of objects (expert specialties) for which forensic expertise is conducted, by typeprocedural proceedings, within which the relevant forensic examination is appointed and conducted, according to the subjects who appoint or order the relevant forensic examination, according to the basis and order of appointment, by the complexity of the conduct, by the number of forensic experts who conduct the examination, by sub objects of implementation. A general basis for the appointment of any type of forensic examination has been established. The task and subject of forensic examination on intellectual property law are defined. Given the task and subject of the court case examination on intellectual property law, the questions that are put to the examination during its appointment are highlighted. In the course of the conducted research, the main conclusions were formulated: the concept of forensic examination on issues of intellectual property law and its specific features were highlighted.